Family History of MI, Smoking, and Risk of Periodontal Disease. (September 2018) - Yu, Y.H.; Doucette-Stamm, L.; Rogus, J.; Moss, K.; Zee, R.Y.L.; Steffensen, B.; Ridker, P.M.; Buring, J.E.; Offenbacher, S.; Kornman, K.; Chasman, D.I.
Periodontal disease (PD) shares common risk factors with cardiovascular disease. Our hypothesis was that having a family history of myocardial infarction (FamHxMI) may be a novel risk factor for PD. Risk assessment based on FamHxMI, conditional on smoking status, was examined given the strong influence of smoking on PD. Exploratory analysis with inflammatory biomarkers and genetic determinants was conducted to understand potential mechanistic links. The Women's Genome Health Study (WGHS) is a prospective cohort of US female health care professionals who provided blood samples at baseline in the Women's Health Study, a 2 × 2 factorial clinical trial investigating vitamin E and aspirin in the prevention of cardiovascular disease and cancer. PD was ascertained via self-report over 12 y of follow-up. Prevalence (3, 442 cases), incidence (1, 365 cases), and survival analysis of PD were investigated for associations of FamHxMI as well as in strata of FamHxMI by smoking. Kruskal-Wallis, chi-square tests, multivariate regression, and Cox proportional hazard models were used for the analyses. In the WGHS, women with FamHxMI showed higher risk of ever having PD. A particularly high-risk group of having both FamHxMI and smoking at baseline was highlighted in the prevalence and risk of developing PD. PD risk increased according to the following strata: no FamHxMI and nonsmokers (reference), FamHxMI and nonsmokers (hazard ratio [HR] = 1.2, 95% CI = 1.0 to 1.5), smokers without FamHxMI (HR = 1.3, 95% CI = 1.2 to 1.5), and smokers with FamHxMI (HR = 1.5, 95% CI = 1.2 to 1.8). An independent analysis by the dental Atherosclerosis Risk in Communities study ( N = 5, 552) identified more severe periodontitis cases among participants in the high-risk group (smokers with FamHxMI). Further examination of interactions among inflammatory biomarkers or genetic exploration with FamHxMI did not explain the risk increase of PD associated with FamHxMI in the WGHS. Future efforts based on an integrative-omics approach may facilitate validation of these findings and suggest a mechanistic link between PD and FamHxMI.